Asep Gym Family ( Perancangan Bisnis Fitness Center ): Indonesia - Asep Sucipto Indra Sukma; Agung Wijoyo; Asep Muhammad Junaedi; Juhaendi Juhaendi; Muhammad Fauzan Sabana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
With the high public awareness of the importance of health and being a healthier life, one of which is obtained by regular exercise, fitness is one of the alternative means to help people exercise which can combine various activities such as weight training to tighten muscles, but balanced with a diet and adequate rest to get maximum results, with many complaints of lack of existing facilities and demand for facilities therefore with this analysis asep gym family is worth making to get business feasibility and results in the future.